Development of Podcast Media As A Social-Support-Based Coping Strategy In Reducing The Level of Work Stress of English Language Teachers at Public High Schools In Bandar Lampung - Wirayuda, Angga; Yulianti, Dwi; Agung, Iskandar (UNDIKMA, 2024)
This study aims to analyze podcast media literature to reduce work stress in English teachers at Bandar Lampung public high school. This research is a literature review research by reviewing 10 relevant articles related to the keywords in this study. The results of the study can be concluded that the development of podcast media as a social support-based coping strategy can be an effective alternative in helping teachers manage work stress. The development of podcast media as a coping strategy based on social support can be an effective alternative in helping teachers manage work stress.. Evaluation of the effectiveness of the podcast media implementation needs to be done to measure changes in teachers' work stress levels. Involving teachers in the development of podcast content is also important to ensure optimal relevance and engagement. The impact of technology on mental health needs to be carefully considered. Collaboration between various parties, including mental health practitioners, researchers, policy makers, and the technology industry, is key in overcoming challenges and utilizing the positive potential of technology in supporting mental health. Thus, the conclusion of this study shows that the development of social support-based coping strategies using podcast media can be an effective solution in managing teachers' work stress. It is important to continue to develop and evaluate the use of this podcast media as a means to improve teachers' well-being and work productivity